On the mechanism of tumor cell entry of aloe‐emodin, a natural compound endowed with anticancer activity. Issue 5 (11th June 2021) - Pecere, Teresa; Ponterio, Eleonora; Di Iorio, Enzo; Carli, Modesto; Fassan, Matteo; Santoro, Luisa; Bissaro, Maicol; Bernabè, Giulia; Moro, Stefano; Castagliuolo, Ignazio; Palù, Giorgio
Abstract: Aloe‐emodin (1, 8‐dihydroxy‐3‐[hydroxymethyl]‐anthraquinone), AE, is one of the active constituents of a number of plant species used in traditional medicine. We have previously identified, for the first time, AE as a new antitumor agent and shown that its selective in vitro and in vivo killing of neuroblastoma cells was promoted by a cell‐specific drug uptake process. However, the molecular mechanism underlying the cell entry of AE has remained elusive as yet. In this report, we show that AE enters tumor cells via two of the five somatostatin receptors: SSTR2 and SSTR5. This observation was suggested by gene silencing, receptor competition, imaging and molecular modeling experiments. Furthermore, SSTR2 was expressed in all surgical neuroblastoma specimens we analyzed by immunohistochemistry. The above findings have strong implications for the clinical adoption of this natural anthraquinone molecule as an antitumor agent.